2014
DOI: 10.4049/jimmunol.1300047
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Ameliorates the Inflammatory Process in Psoriasis by Suppressing Proinflammatory Cytokine Production

Abstract: IL-37 is a potent inhibitor of innate immunity by shifting the cytokine equilibrium away from excessive inflammation. Psoriasis is thought to be initiated by abnormal interactions between the cutaneous keratinocytes and systemic immune cells, triggering keratinocyte hyperproliferation. In the current study, we assessed IL-37 in two well-known psoriasis models: a human keratinocyte cell line (HaCaT) and the keratin 14 VEGF-A–transgenic mouse model. First, we used the HaCaT cell line, which was transiently trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
136
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 59 publications
8
136
2
1
Order By: Relevance
“…The inhibitory effects of IL-37 on innate immune response have been studied using cells transfected or silenced with IL-37, mice treated with recombinant or plasmid-DNA IL-37, and IL-37tg mice (2,3,(8)(9)(10)(11)(12). In the present study, we not only demonstrated the inhibitory effects of IL-37 on adaptive immune response, but also provided evidence that IL-37 promotes generation of semimature tolerogenic DCs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The inhibitory effects of IL-37 on innate immune response have been studied using cells transfected or silenced with IL-37, mice treated with recombinant or plasmid-DNA IL-37, and IL-37tg mice (2,3,(8)(9)(10)(11)(12). In the present study, we not only demonstrated the inhibitory effects of IL-37 on adaptive immune response, but also provided evidence that IL-37 promotes generation of semimature tolerogenic DCs.…”
Section: Discussionsupporting
confidence: 63%
“…Administration of recombinant human IL-37 in mice suppresses cytokine and chemokine production, neutrophil infiltration, and cell death, thereby ameliorating hepatic and myocardial ischemia/reperfusion injury (9,10). Treatment of mice with human IL-37 plasmid-DNA reduces local and systemic inflammation in Con A-induced hepatitis and psoriasis (11,12).…”
mentioning
confidence: 99%
“…In vivo, mice transgenic for IL-37 exhibited markedly reduced production of IL-17 and other proinflammatory cytokines, including IL-1b and IL-6, following LPS stimulation (11). Other studies showed that IL-37 is strongly expressed by CD4 + T cells and macrophages in human psoriatic plaques, which may inhibit the excessive inflammation in the pathogenesis of psoriasis (12). Based on the data described above, it is postulated that IL-37, through the production of activated immune cells, may play a prominent role in the pathogenesis of RA by curbing IL-17 or other proinflammatory cytokines.…”
mentioning
confidence: 99%
“…2 Although its biological function is not elucidated completely, many studies indicate a protective role of IL37 on immunopathogenesis through reducing anti-inflammatory cytokines from innate immune cells. 22 Here to better understand this Figure 3 The dN/dS ratios of different evolutionary lineages in primates. Phylogenetic tree was constructed using neighbor-joining method using IL37 orthologous sequences from multiple species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that the biological functions of IL37 variants need to be verified and compared with earlier experimental results using NCBI reference protein. 4,8,22 Second, our data provides valuable guidance on picking SNPs for disease association studies. Previous reports suggested that IL37 was involved in the development of various inflammatory conditions, including ankylosing spondylitis and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%